Irrigation of radish cultivars in the region of Viçosa, Minas Gerais, Brazil (Revista Ciência Agronômica, 2019)
The region of Viçosa in Brazil stands out for vegetable production. For success in this activity, the correctchoice of cultivar with the correctly applied irrigation are necessary. As such, the aim of this study was to evaluate theagronomic performance of radish cultivars submitted to different irrigation depths. The radish crop was grown in a protectedenvironment over three cycles, for periods of 38 to 40 days. The experimental design was of randomised complete blocks insplit plots with five replications, comprising five irrigation depths (50, 75, 100, 125 and 150% of crop evapotranspirationETc) in the plots, with three radish cultivars in the subplots. (Hybrid no 25 - Sakata, Crunchy Royale - Sakata and VipCrimson - Feltrin). A drip irrigation system was used, with the ETc obtained by means of the GESAI method. The followingparameters were evaluated: root depth, plant water potential, leaf temperature, leaf weight, root diameter and length, numberand weight of commercial and non-commercial roots, and water use efficiency. Since the experimental soil presented highwater retention and availability, greater than 1.8 mm cm-1, an irrigation depth of 50% ETc is recommended, provided thatthe soil is at field capacity at the start of the cycle. When considering productivity and quality, the Crunchy Royale cultivaris recommended when cultivating the radish in Viçosa, Brazil.